2017
DOI: 10.1371/journal.pone.0170823
|View full text |Cite|
|
Sign up to set email alerts
|

Phenolic extract from oleaster (Olea europaea var. Sylvestris) leaves reduces colon cancer growth and induces caspase-dependent apoptosis in colon cancer cells via the mitochondrial apoptotic pathway

Abstract: Dietary polyphenols, derived from natural products, have received a great interest for their chemopreventive properties against cancer. In this study, we investigated the effects of phenolic extract of the oleaster leaves (PEOL) on tumor growth in mouse model and on cell death in colon cancer cell lines. We assessed the effect of oleaster leaf infusion on HCT116 (human colon cancer cell line) xenograft growth in athymic nude mice. We observed that oleaster leaf polyphenol-rich infusion limited HCT116 tumor gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 45 publications
2
18
0
2
Order By: Relevance
“…Among these compounds, polyphenols, secondary metabolites of plants that have beneficial effects on human health and reduce the risk of most cancers, have been widely recognized. 22 , 23 Hydroxytyrosol is a natural polyphenol compound and a strong antioxidant. Recent studies have shown that this potent antioxidant has several biological activities, such as oxidative-stress control, cellular efficacy, and induction of apoptosis in several tumor-cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Among these compounds, polyphenols, secondary metabolites of plants that have beneficial effects on human health and reduce the risk of most cancers, have been widely recognized. 22 , 23 Hydroxytyrosol is a natural polyphenol compound and a strong antioxidant. Recent studies have shown that this potent antioxidant has several biological activities, such as oxidative-stress control, cellular efficacy, and induction of apoptosis in several tumor-cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The early pro survival response inhibits the expression of pro apoptotic C/EBP homologous protein (CHOP). However, prolonged ERS is associated with an increase of ROS levels and IRE-1α/XBP1 mediated activation of both CHOP and Bim and inhibition of Bcl-2, which leads to apoptosis [ 85 , 86 , 87 , 88 , 89 ]. Activation of the PERK pathway leads to phosphorylation of eukaryotic initiation translation factor 2α (eIF2α), which triggers an antioxidant, pro survival response mediated by transcription factor 4 (ATF4).…”
Section: Er Stress Induction and Consequencesmentioning
confidence: 99%
“…In CRC cell lines, treatment of Phenolic, the extract of the oleaster leaves (PEOL), increases ER stress-mediated apoptosis. The effect of PEOL was inhibited as the usage of ROS scavengers, indicating the involvement of ROS in PEOL induced apoptosis(Zeriouh et al, 2017). Triptolide (PG490) induced apoptosis through ROS in a time-and dose-dependent manner(Tan & Chiu, 2013).Except for showing a cytotoxic effect on CRC cell lines, PG490 also enhanced the cytotoxicity effect of 5-fluorouracil (5-FU) in CRC cell lines in 4-15fold.…”
mentioning
confidence: 99%